Unraveling the path to osteoarthritis management: targeting chondrocyte apoptosis for therapeutic intervention - Lee, Yi Ting; Mohd Yunus, Mohd Heikal; Yazid, Muhammad Dain; Ugusman, Azizah (Frontiers in Cell and Developmental Biology, 2024)
Osteoarthritis (OA) is a chronic disease affecting joints and further causing disabilities. This disease affects around 240 million people worldwide. It is a multifactorial disease, and its etiology is difficult to determine. Although numerous therapeutic strategies are available, the therapies are aimed at reducing pain and improving patients’ quality of life. Hence, there is an urgent need to develop disease-modifying drugs (DMOAD) that can reverse or halt OA progression. Apoptosis is a cell removal process that is important in maintaining homeostatic mechanisms in the development and sustaining cell population. The apoptosis of chondrocytes is believed to play an important role in OA progression due to poor chondrocytes self-repair abilities to maintain the extracellular matrix (ECM). Hence, targeting chondrocyte apoptosis can be one of the potential therapeutic strategies in OA management. There are various mediators and targets available to inhibit apoptosis such as autophagy, endoplasmic reticulum (ER) stress, oxidative stress, and inflammation. As such, this review highlights the importance and potential targets that can be aimed to reduce chondrocyte apoptosis.